2019
DOI: 10.1093/eurheartj/ehz056
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for cardiovascular medicine: a practical primer

Abstract: Deep learning (DL) is a branch of machine learning (ML) showing increasing promise in medicine, to assist in data classification, novel disease phenotyping and complex decision making. Deep learning is a form of ML typically implemented via multi-layered neural networks. Deep learning has accelerated by recent advances in computer hardware and algorithms and is increasingly applied in e-commerce, finance, and voice and image recognition to learn and classify complex datasets. The current medical literature sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
175
0
16

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(191 citation statements)
references
References 91 publications
0
175
0
16
Order By: Relevance
“…Experimental studies have investigated a net-Recently, in medical imaging, we have assisted with a shift from qualitative imaging to quantitative assessment through the extraction of imaging biomarkers by applying artificial intelligence 81) . Machine and deep learning approaches involve using raw imaging data to extrapolate imaging features and, together with clinical information and big data, are processed into algorithms to build disease models and neural networks in order to improve diagnosis, make clinical decisions, and predict outcomes towards a personalized medical approach 81) . Recent studies on machine learning approaches exploiting CTCA showed high prognostic accuracy in risk stratification and prediction of mortality in CHD patients [82][83][84] .…”
Section: Personalized Therapy For Primary Prevention and Secondary Prmentioning
confidence: 99%
“…Experimental studies have investigated a net-Recently, in medical imaging, we have assisted with a shift from qualitative imaging to quantitative assessment through the extraction of imaging biomarkers by applying artificial intelligence 81) . Machine and deep learning approaches involve using raw imaging data to extrapolate imaging features and, together with clinical information and big data, are processed into algorithms to build disease models and neural networks in order to improve diagnosis, make clinical decisions, and predict outcomes towards a personalized medical approach 81) . Recent studies on machine learning approaches exploiting CTCA showed high prognostic accuracy in risk stratification and prediction of mortality in CHD patients [82][83][84] .…”
Section: Personalized Therapy For Primary Prevention and Secondary Prmentioning
confidence: 99%
“…All these algorithms have been mostly used in the fields of imaging, clinical-risk stratification, and precision medicine. 16 Two of the supervised learning techniques are neural networks and deep learning. Neural networks that process solutions as a brain would do, have been used successfully to classify cardiac abnormalities.…”
Section: Central Messagementioning
confidence: 99%
“…There is a need for machine learning and deep learning algorithms associated with high computational capacities. For clinicians, understanding machine learning ‘black boxes’ and to be confident in clinical decisions and therapeutic allocations proposed by AI is fascinating but troublesome . Performance in the development of such algorithms demands a strong collaboration between clinicians and data scientists from the precise formulation of problems to a common and balanced interpretation of results .…”
Section: The Challenges Of Big Datamentioning
confidence: 99%